1978
DOI: 10.1172/jci109246
|View full text |Cite
|
Sign up to set email alerts
|

Active release of human platelet factor VIII-related antigen by adenosine diphosphate, collagen, and thrombin.

Abstract: A B S T R A C T Platelet Factor VIII-related antigen (VIIIR:Ag) represents a significant proportion of the total circulating VIIIR:Ag pool. However, its participation in the events of primary hemostasis has not been shown. We now report that platelet-contained VIIIR:Ag is released from platelets by collagen, ADP and thrombin. The concentrations of these agonists, required for VIIIR:Ag release, are the same or lower than those required for release of serotonin, lysosomal enzymes, or fibrinogen. This release has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
2

Year Published

1979
1979
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(58 citation statements)
references
References 27 publications
2
53
1
2
Order By: Relevance
“…2 a). The granular pattern of staining was similar to that found in platelet alpha granules (Fig. 2, e and f), which are known to contain vW protein (14,15).…”
Section: Resultssupporting
confidence: 76%
“…2 a). The granular pattern of staining was similar to that found in platelet alpha granules (Fig. 2, e and f), which are known to contain vW protein (14,15).…”
Section: Resultssupporting
confidence: 76%
“…In addition, TGF␤ platelets contain in their alphagranules numerous proteins, including adhesion factors, plasma proteins, coagulation factors, protease inhibitors (Davey and Luscher, 1968;Levine and Wohl, 1976;Nachman and Harpel, 1976;Koutts et al, 1978;Zucker et al, 1979;Plow and Collen, 1981), and the growth factors PDGF (Antoniades et al, 1979;Heldin et al, 1981), EGF/TGF␣ (Oka and Orth, 1983), and IGF . All three isoforms of PDGF, the AB heterodimer and the AA and BB homodimers, have been isolated from human platelets.…”
Section: Platelet-derived Growth Factors Stimulate Pancreatic Stellatmentioning
confidence: 99%
“…While this study was in progress [25], Tracy et al [26] reported immunologic similarity of bovine platelet factor V to plasma factor V by immunodiffkion and radioimmunoassay, but no data were presented as to the molecular weight or electrophoretic migration. The similarity of platelet fibrinogen [27], factor VIII/vWf [28], the a subunits of factor XI11 [29], and fibronectin [30] to the corresponding plasma proteins has been demonstrated. Platelet factor V solubilized by a nonionic detergent in the presence of proteolytic and metabolic inhibitors exhibits and anodal mobility on immunoelectrophoresis.…”
Section: Discussionmentioning
confidence: 99%